THE RELATIONSHIP OF EDUCATION AND TRAINING (THE TRAINING) WITH WORK ACHIEVEMENT OF EMPLOYEES AT AMEN CAMAT OFFICE LEBONG DISTRICT - Evriani; Neri Susanti; Zahrah Indah Ferina (Penerbit Jurnal Indonesia, 2020)
Target of this research is to know relation Education and Training with the performance of goverment employees at the Office at Office Regency Chief Amen of Lebong of Resort of Lebong. Method Analysis the used is correlation of rank hypothesis test and spearman with comparison of value of rho test. There are relationwhich is significant between education with officer performance at Office Regency Chief of Amen of Province of Lebong.